Peningkatan Motivasi Belajar Calon Guru IPA dengan Pembelajaran Kooperatif Tipe Two Stay Two Stray - Astuti Wijayanti; Eka Aji Purwanto (Jurnal Ilmiah Profesi Guru (JIPG), 2021)
Abstract: This Classroom Action Research aims to describe Two Stay Two Stray (TSTS) to increase the learning motivation of prospective science teachers. The subjects of this study were the first semester IPA Education students of Sarjanawiyata Tamansiswa University, totaling 47 people. The object of this research is learning by using the Two Stay Two Stray type cooperative model and learning motivation. Data collection techniques in this study used learning motivation questionnaires, lecturer observation sheets, and student observation sheets. Data analysis techniques use percentage scores for each indicator of learning motivation. The results of the study show that the learning motivation of prospective science teachers is increasing. The average results of observations of student motivation in the first cycle were 72.19% and increased in the second cycle by 88.03%. Keywords: Two Stay Two Stray Model, Motivation